Acquis Schengen on Ukraine’s path to European integration - Nikiforenko, Volodymyr; Oliinyk, Svitlana (Migration & Law, 2026)
This article outlines the strategic vision, core principles, objectives, institutional mechanisms, and general direction of Ukraine’s Schengen Action Plan on its path to full membership in the European Union. It is determined that the implementation of the Schengen management system in Ukraine requires the involvement of representatives from relevant ministries, other central executive bodies, and the expert community. To define the strategic vision, core principles, objectives, and institutional mechanisms, a Framework for the Schengen Action Plan for Ukraine must be approved. It has been established that it is advisable to organize the work of interagency expert working groups by areas of the Schengen Acquis (border control, visa policy, migration and asylum, police cooperation, judicial cooperation, the Schengen Information System, and personal data protection), with the mandatory involvement of experts from European Union institutions.